Effect of Inoculum Levels and Sugar Concentrations on the Preparation of Fermented Semi-dry Fish Sausages - V.R, Joshi; T.M., Rudra Setty (Fishery Technology, 2025)
Fermented semi-dry fish sausages were prepared with different levels of lactic acid (LAB) inoculum (Il’/g, 107/g and 108/g) and sugar (1.0% to 5.0%) and subjected to chemical and organoleptic evaluation. Higher levels of LAB inoculum resulted in faster fermentation rate. Growth of LAB decreased at higher rates of LAB inoculum. At lower levels of LAB in- oculum, TPC, TMA and TVB values were higher. There was no significant difference among the different levels of LAB inoculum with respect to organoleptic quality, but lower scores were received for the high inoculum level. Fermentation rate was not affected by the different levels of sugar and 1% sugar level was preferred by the panelists.